Peran Bidang Intelijen Kejaksaan Negeri Pematangsiantar Dalam Penegakkan Hukum - Sesilia, Paskah; Anggusti, Martono (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
The Intelligence Division of the Pematangsiantar District Prosecutor's Office plays a key role in supporting leadership by conducting investigations, ensuring security, and mobilizing resources to prevent criminal activities. Research on its role highlights its legal and structural significance, analyzed using normative-juridical methods. Operating under the Attorney General's leadership, which oversees seven Deputies, a Training and Education Agency Head, and 33 Provincial Prosecutor’s Offices, the division supports law enforcement efforts nationwide.Law Number 11 of 2021 underscores the Attorney General's Office as a central and strategic institution for national resilience, acting as a mediator between investigations and court proceedings, as well as executing court decisions. The Intelligence Division is supported by national intelligence agencies, which provide operational assistance in investigations, security, and data management, alongside technological advancements to enhance intelligence capabilities and ensure effective law enforcement.